Profile and business practices of entrepreneurs in the small-scale food service businesses in Manila - Honorio, Angela E.
The purpose of this study was to identify unique characteristics of entrepreneurs who are engaged in the small-scale food service industry and to examine relationships between their personal background, personality traits, and business practices. A 10 percent sample was taken from a population of 8,853 entrepreneurs in Manila. Data were obtained through a questionnaire sent by mail. Of the 885 questionnaires sent, 105 were returned by the post office as undelivered. There were 109 responses of which 103 were usable for a response rate of 13.2 percent. From the entrepreneur's answers to the four-page instrument, a profile of the food service entrepreneur in the small-scale industry was developed. The personality trait statements were grouped using factor analysis into the 6 core personality factor traits; namely, self-confidence and optimism, flexibility, risk-taking ability, energy level and drive to achieve, creativity and innovation and independence and initiative. The business practice statements were grouped into 7 dimensions namely, Human resources Development (HRD) and Employee Relations, Marketing, Cost Control, Social Responsibility, Finance, Customer Relations, and Menu Planning. Using t-tests and correlation analysis, three hypotheses were tested to determine whether significant relationships existed between the 6 personality factor traits, the 7 business dimensions and the age, sex, racial descent, educational level, number of years of schooling and the number of years as an entrepreneur in the food service business (which are selected variables of the personal background). At 5 percent level of significance, relationships existed among the the entrepreneur's gender with respect to marketing practices and the entrepreneur's education with respect to financial management practices. Other significant relationships that existed were between the entrepreneur's flexibility, with respect to marketing and customer relations practices; risk-taking ability with respect to cost control; energy level and drive to achieve with respect to marketing, cost control and finance; creativity and innovation with respect to social responsibility, finance and menu planning; and independence and initiative with respect to social responsibility. Significant relationships also existed between the entrepreneur's risk-taking ability with respect to educational level as well as independence and initiative with respect to the number of years of schooling. The findings of the study warrant that similar studies be undertaken to enhance the meager knowledge available on entrepreneurs in the food service business. Further studies can focus on the environment, organization, and processes these individuals and their respective food service businesses operate in. Other studies may focus on the different sizes of the food service industry and the primary issues affecting the development and growth of these businesses. Studies on developing a training program and evaluating entrepreneurial performance should also be considered. Considering the role these entrepreneurs and their respective food service businesses play in the economic development of the Philippines, it bis further recommended that government policy makers support, and design more effective programs aimed at providing better assistance to these businesses within the industry.